Deinococcus psychrotolerans sp. nov., isolated from soil on the South Shetland Islands, Antarctica - Tian, Jin; Wang, Liqiu; Liu, Ping; Geng, Yingchao; Zhu, Guoxin; Zheng, Ruichen; Liu, Zuobing; Zhao, Yiming; Yang, Jian; Peng, Fang (International Journal of Systematic and Evolutionary Microbiology, 2019)
A Gram-stain-negative, non-motile, strictly aerobic, coccus-shaped bacterium, designated S14-83(T), was isolated from a soil sample collected from the South Shetland Islands of Antarctica. Phylogenetic analysis based on 16S rRNA gene sequences indicated that the strain is a novel member of the genus Deinococcus, with Deinococcus alpinitundrae as its closest relative (96.1 % similarity). The DNA G+C content of the strain was 61.1 mol% and the major respiratory quinone was MK-8. Major cellular fatty acids were summed feature 3 (C-16:1 omega 7c/C-16:1 omega 6c) and C-16:0. As well as containing glycophospholipid, aminophospholipids and glycolipid as major polar lipids, there were also some unknown polar lipids. The diagnostic diamino acid in the cell-wall peptidoglycan was ornithine, corroborating the assignment of the strain to the genus Deinococcus. Strain S14-83(T) was shown to be extremely resistant to gamma radiation (>10 kGy) and UV light (460 Jm(-2)). On the basis of phylogenetic, chemotaxonomic and phenotypic data presented here, strain 514-83(T) represents a novel species of the genus Deinococcus, for which the name Deinococcus psychrotolerans sp. nov. is proposed. The type strain is S14-83(T) (=CCTCC AB 2015449(T) = DSM 105285(T)).